Improved strength and recovery after velocity-based training: a randomized controlled trial - Held, S.; Hecksteden, A.; Meyer, T.; Donath, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The present intervention study examined the effects of intensity-matched velocity-based strength training with a 10% velocity loss (VL10) versus traditional 1-repetition maximum (1RM) based resistance training to failure (TRF) on 1RM and maximal oxygen uptake (VO2max) in a concurrent training setting.